Effect of Spalling Shape on Meshing Stiffness and Dynamics Characteristic of Gear - Tu Xuxin; Jian Xiaochun; Wu Shengli (Jixie chuandong)
The traditional research on spalling gear failure mainly focuses on the change of gear stiffness under different spalling depth and width，it has great limitations. Aiming at this problem，the influence of spalling shape and the spalling shape distribution on gear stiffness and dynamics is studied. To begain with，the spalling position is at the place which on the pitch circle of the gear，different spalling shapes are taken at this position. Then，on the basis of the traditional potential energy method，considering the change of spalling width when the meshing position of gears changes，the stiffness curves of different spalling patterns are obtained. Combined with the dynamics changes，the vibration acceleration signals of different faults are analyzed， which shows that the spalling shape factors affect the gear related indicators，making it difficult to distinguish the spalling gear from the normal gear，and the indicators overlap with each other. The method of combined probability density function with kurtosis value is proposed，and the probability density function curve is used to judge the gear fault state. It is found that this method can effectively counteract the interference of shape factor on the index，and has high feasibility and discrimination ability.